PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN TEKNIK BRAINSTORMING UNTUK MENINGKATKAN KEMAMPUAN ANALISIS MAHASISWA PADA MATA KULIAH TEORI HUKUM DAN KONSTITUSI - Cahyono, Cahyono; Sukarliana, Lili; Mulyana, Dadang; Deni Normansyah, Asep (STKIP Subang, 2019)
The learning process in law theory and constitution courses requires variations in the use of learning models, to increase the level of understanding and analysis of student abilities related to concepts and theories of law theory and constitution courses. The purpose of this study is to learn how to apply the problem-based learning model of learning using brainstorming techniques in improving the analysis skills of students specifically with respect to lectures on legal theory and constitution courses. Quantitative research with the main data source is pretest and posttest research with research subjects of all 5 semester students of PPKn study programs taking courses in legal theory and constitution. The results showed that there was an increase in student scores seen from the results of the pretest and posttest scores which increased significantly, the highest value at the posttest score reached 92 and the highest value at the pretest score 76. It can be concluded that the need for a problem based learning learning model with brainstorming techniques proved to be effective in improving students' analytical skills regarding legal theory and constitution.